Acute Zika Virus Infection in an Endemic Area Shows Modest Proinflammatory Systemic Immunoactivation and Cytokine-Symptom Associations - Barros, Jéssica Barletto de Sousa; Silva, Paulo Alex Neves da; Koga, Rosemary de Carvalho Rocha; Gonzalez-Dias, Patrícia; Carmo Filho, José Rodrigues; Nagib, Patrícia Resende Alo; Coelho, Verônica; Nakaya, Helder I.; Fonseca, Simone Gonçalves; Pfrimer, Irmtraut Araci Hoffmann (Frontiers in Immunology, 2018)
An early immune response to Zika virus (ZIKV) infection may determine its clinical manifestation and outcome, including neurological effects. However, low-grade and transient viremia limits the prompt diagnosis of acute ZIKV infection. We have investigated the plasma cytokine, chemokine, and growth factor profiles of 36 individuals from an endemic area displaying different symptoms such as exanthema, headache, myalgia, arthralgia, fever, hyperemia, swelling, itching, and nausea during early-phase infection. These profiles were then associated with symptoms, revealing important aspects of the immunopathophysiology of ZIKV infection. The levels of some cytokines/chemokines were significantly higher in acute ZIKV-infected individuals compared to healthy donors, including interferon gamma-induced protein 10 (IP-10), regulated on activation, normal T cell expressed and secreted (RANTES), interferon-γ, interleukin (IL)-9, IL-7, IL-5 and IL-1ra, including some with predominantly immunoregulatory activity. Of note, we found that higher levels of IP-10 and IL-5 in ZIKV-infected individuals were strongly associated with exanthema and headache, respectively. Also, higher levels of IL-1ra were associated with subjects with arthralgia, whereas those with fever showed lower levels of G-CSF. No correlation was observed between the number of symptoms and ZIKV viral load. Interestingly, only IP-10 showed significantly decreased levels in the recovery phase. In conclusion, our results indicate that acute ZIKV infection in a larger cohort resident to an endemic area displays a modest systemic immune activation profile, involving both proinflammatory and immunoregulatory cytokines and chemokines that could participate of virus control. In addition, we show that differential cytokine/chemokine levels are related to specific clinical symptoms, suggesting their participation in underlying mechanisms.